Lesion evolution after gamma knife irradiation observed by magnetic resonance imaging - Jirák, D; Námĕstková, K; Herynek, V; Liscák, R; Vymazal, J; Mares, V; Syková, E; Hájek, M (International journal of radiation biology, 2007)
PURPOSE: Our study is focused on the magnetic resonance imaging (MRI) observation of lesion development and hippocampus related functional impairments in rats after irradiation with a Leksell Gamma knife (LGK). MATERIALS AND METHODS: We exposed 32 three-month-old Long-Evans rats to various radiation doses (25 Gy, 50 Gy or 75 Gy). The rats were scanned by a 4.7 T magnetic resonance (MR) spectrometer at several timepoints (1 - 18 months) after irradiation. The lesion size was evaluated by manual segmentation; the animals were behaviorally tested in a Morris water maze and examined histologically. RESULTS: We found that a dose of 25 Gy induced no edema, necrosis or behavioral change. The response of the rats to higher doses was not uniform; the first occurrence of lesions in the rat brains irradiated with 50 and 75 Gy was detected six months post-irradiation. Functional impairment correlated well with the lesion size and histology. CONCLUSIONS: Rat brains showed the development of expanding delayed lesions after 50 or 75 Gy doses from the LGK during the first year after irradiation.
Keywords: Magnetic Resonance Imaging; radiační poranění; poranění mozku; magnetická rezonanční tomografie; vztah dávky záření a odpovědi; Dose-Response Relationship, Radiation; Radiation Injuries; krysa rodu Rattus; Hippocampus; zvířata; hipokampus; Rats, Long-Evans; radiochirurgie; Radiosurgery; Male; dávka záření; potkani Long-Evans; Rats; Radiation Dosage; Animals; Brain Injuries; mužské pohlaví